2005
DOI: 10.1007/s10562-005-7431-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Selectivity Control in Reductive Amination of Butyraldehyde over Noble Metal Catalysts

Abstract: Approaches to control selectivity and activity in the catalytic reductive amination of butyraldehyde with ammonia over carbon supported noble metal catalysts (Ru, Rh, Pd, and Pt) were explored. Detailed analysis of the reaction network shows that the Schiff base N-[butylidene]butan-1-amine is the most prominent initial product and, only after nearly all butyraldehyde had been converted to N-[butylidene]butan-1-amine, amines are detected in the product mixture. From this intermediate, good hydrogenolysis cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…Thus, amination and hydrogenolysis of the Schiff base towards a primary amine was the dominant pathway at high temperature. These results were also in agreement with the literature [33]. The results of our experiments also showed that only very little 2c was formed in the catalysis system when the Ru/γ-Al2O3 was used as the catalyst, which may be due to the weak chemisorption of 2b intermediate on the Ru/γ-Al2O3 surface, resulting in a low rate of hydrogenation to 2c.…”
Section: Reaction Pathwayssupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, amination and hydrogenolysis of the Schiff base towards a primary amine was the dominant pathway at high temperature. These results were also in agreement with the literature [33]. The results of our experiments also showed that only very little 2c was formed in the catalysis system when the Ru/γ-Al2O3 was used as the catalyst, which may be due to the weak chemisorption of 2b intermediate on the Ru/γ-Al2O3 surface, resulting in a low rate of hydrogenation to 2c.…”
Section: Reaction Pathwayssupporting
confidence: 92%
“…The yield of 2b was about 77% at 40 °C, which declined to 0.1% when the reaction temperature increased from 40 °C to 80 °C. The similar Schiff base intermediate was also found in the previous studies [20,33,38]. A closer look was taken to analyze the products after the reaction at 80 °C.…”
Section: Reaction Pathwayssupporting
confidence: 81%
See 3 more Smart Citations